Free Willy - Strasser, Todd.; Walker, Keith A.; Blechman, Corey (New York : Scholastic, 1993)
Eleven-year-old Jesse tries to find a way to free his new friend, a 7,000-pound killer whale named Willy, from a miserable existence as the star attraction at an amusement park.
Keywords: Killer whale -- Fiction; Whales -- Fiction; Captive wild animals -- Fiction; Animals -- Treatment -- Fiction